Study on clinical profile, risk factors, morbidity and mortality patterns of intrauterine growth restricted babies admitted in neonatal intensive care unit of tertiary care hospital, Vijayapura - Lifam, Asiya; Malagi, Naushad Ali N.; Thobbi , A. N. (International Journal of Contemporary Pediatrics, 2024)
Background: Intrauterine growth restriction (IUGR) is an important clinical problem associated with increased perinatal mortality and morbidity. The neonate may be either constitutionally small or small due to pathophysiological changes with maternal, placental or foetal factors involved. A foetus with IUGR has not achieved its genetic growth potential. In addition, emerging evidence suggests that they are also more likely than normal weight babies to suffer from degenerative diseases like hypertension, diabetes and cardiovascular diseases in adulthood. Methods: This is a cross-sectional study carried out in the neonatal unit, tertiary care hospital, Vijayapura. This study was carried out between April 2022 to April 2024. 120 IUGR babies were included in this study. Results: Of the 120 babies 22 (18.3%) have died in the hospital. 19 (15.5%) have been discharged with abnormal neurological examination and 79 (66.3%) have been discharged with good condition at discharge condition. Morbidity pattern of IUGR shows that hypoglycaemia (63.3%) and perinatal asphyxia (45.0%) are the commonest complication. Other commoner are sepsis (33.3%), hypocalcaemia (30.0%), hypothermia (28.3%) and thrombocytopenia (25.0%). Conclusions: Perinatal asphyxia and meconium aspiration are significantly associated with abnormal neurological examination at discharge. Perinatal asphyxia, pulmonary haemorrhage and persistent PH are significantly associated with death during the hospital stay. 73 (77.5%) mothers had one or more risk factors. Malnutrition is the commonest (40.0%), other are anaemia (34.2%), pregnancy-induced hypertension (PIH) (18.3%), multiple gestations (8.3%) and lower age of the mother.